Hydrolases on fumed silica: conformational stability studies to enable biocatalysis in organic solvents - Cruz Jimenez, Juan Carlos (Kansas State University, 2010)
One area of considerable importance in modern biotechnology is the preparation of highly active and selective enzyme based biocatalysts for applications in organic solvents. A major challenge is posed by the tendency of enzymes to cluster when suspended in organic solvents. Because the clusters obstruct the transport of substrates to the active site of the enzyme, the observed activity is often severely reduced. Over the past two decades, many strategies have been proposed to mitigate this problem. We have tackled this major hurdle by devising an immobilization strategy that utilizes fumed silica as carrier for the enzyme molecules. Fumed silica is a non-porous nanoparticulated fractal aggregate with unique absorptive properties. The enzyme/fumed silica preparation is formed in two steps. The buffered enzyme molecules are physically adsorbed on the fumed silica and then lyophilized. This protocol was shown to be successful with two enzymes of industrial relevance, Candida antarctica Lipase B (CALB) and subtilisin Carlsberg. The maximum observed catalytic activity in hexane reached or even exceeded commercial immobilizates and nonbuffer salt based preparations. The results demonstrated that catalytic activity has an intricate relationship with the nominal surface coverage (%SC) of the support by the enzyme molecules. s. Carlsberg exhibited an ever increasing activity as more surface area was provided per enzyme molecule. The activity leveled off when a sparse surface population was reached. CALB showed a maximum in catalytic activity at an intermediate surface coverage with steep decreases at both lower and higher surface coverage. It was shown that this maximum results from the presence of three distinct surface loading regimes after lyophilization: 1. a low surface coverage where opportunities for multi-attachment to the surface likely lead to detrimental conformational changes, 2. an intermediate surface coverage where interactions with neighboring proteins and the surface help to maintain a higher population of catalytically competent enzyme molecules, and 3. a multi-layer coverage where mass transfer limitations lead to a decrease in the apparent catalytic activity. Conformational stability analyses with both fluorescence and CD spectroscopy showed evidence that these regimes are most likely formed during the adsorption step of our protocol. A low conformational stability region was detected at low surface coverage while adsorbates with highly stable enzyme ensembles were observed at high surface coverage. Secondary structural analysis of the lyophilized nanobiocatalysts with FTIR confirmed a substantial decrease in the alpha-helical components at low surface coverage. In summary, the work presented here traces the phenomenological observation of the catalytic behavior of a nanobiocatalyst to molecular-level: enzyme-enzyme and enzyme-support interactions, which are specific to the intricate properties of the enzyme molecules.
Keywords: Biocatalysis; Unfolding; Protein-surface interactions; Conformational stability; Adsorption; Fumed silica; Biophysics, General (0786); Engineering, Chemical (0542)